Divorcio de padres y sus consecuencias en el desarrollo psicosocial de un joven de 21 años - Bravo Riofrio, Daleska Eliana (2021)
The divorce or separation of a couple with children puts an end to the coexistence of both parents together with their children. There can be multiple causes for a divorce, some consequences can be short and long term for the children, especially in those cases in which the divorce has been conflictive. On the other hand, it can have consequences in adult life, presenting a greater risk of psychiatric pathologies or difficulties in interpersonal relationships if an intervention is not carried out that addresses some potentially traumatic situations for the children. The behaviors that are manifested in children as a result of divorce and parental conflict will depend on the age and stage of development of the child, and it is important to recognize them in order to intervene appropriately. The present case study proposes to identify what the psychosocial consequences are and how this situation affects the children of divorced parents, by means of which to be able to identify the psychological pathologies that occur, give a diagnosis and a therapeutic plan. visible and at the same time confirm with the tests that were applied to the young person and determined that this influences emotions and changes in mood, in their personal relationships, becomes depressed and with low self-esteem and if adequate treatment is not done, it could to make fatal decisions, to mitigate the psychological symptoms it was decided to formulate a therapeutic scheme based on cognitive-behavioral therapy.